Uji Kuantitas Kadar Antioksidan dan Kandungan Vitamin C Kombucha Secang (Caesalpinia sappan L.) dengan Pemanis Stevia berdasarkan Variasi Lama Fermentasi - Fadhila Qutrunnadakhairunnisa; Ambarwati Ambarwati; Puji Kurnia Wulan Suci (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2024)
This study aimed to determine the antioxidant levels and vitamin C content of secang kombucha with stevia sweetener based on variations in fermentation time. This research used experimental methods and a Completely Randomized Design with 1 factor, namely fermentation time of 11 days and 13 days with 3 replications each. Data analysis uses quantitative descriptive methods. The results of the research showed that the antioxidant content of secang wood kombucha with stevia sweetener was the highest in the 13 day fermentation treatment, namely 79.14%. Meanwhile, the highest vitamin C content of secang wood kombucha with stevia sweetener was in the 13 day long fermentation treatment, namely 39.14 mg/100g. Keywords: Antioxidants, Fermentation, Kombucha, Secang, Vitamin C